Chronology Protection in the Physical Universe - Austin, James C (Current Research Progress in Physical Science Vol. 5, 2024)
The apparent causal stability of physical reality, from a human perspective, has persisted throughout recorded history. This, however, has not limited the human imagination, and the question of whether it is possible to defy causality in some way has been a serious consideration amongst scientists and philosophers since the late nineteenth century. Attempts to model or simulate violations of causality from known physical principles will either establish the practical possibility of creating a closed timelike path or if not, will immeasurably increase our understanding of the physical world. In this work, earlier findings were considered in order to clarify their arguments and conclusions. This is particularly the case in relation to Hawking’s Chronology Protection Conjecture and the requirement of exotic matter to establish a causality violation in singly connected (3+1) space-time. It is also seen that by generating an asymmetric traversable wormhole, it is possible to create a closed timelike path without the need for exotic matter. However, it is also tentatively concluded such wormholes are likely to be unstable at their initial formation.